2013
DOI: 10.1016/j.chiabu.2013.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Child physical abuse risk moderates spontaneously inferred traits from ambiguous child behaviors

Abstract: The present study examined whether parents at high-risk for child physical abuse (CPA) differed from low-risk parents in their tendency to infer positive traits and negative traits from children’s behaviors. The final sample consisted of 58 (25 low CPA risk and 33 high CPA risk) parents. Parents completed a false-recognition task, which involved viewing behavior descriptions paired with child photographs. Half of the behavior descriptions vaguely/strongly implied a trait and half of the implied traits were pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…After omissions, data from 100 parents were included in the final sample. This rate of exclusion due to invalid CAP inventories is consistent with exclusion rates observed in previous research (e.g., Carr, Moretti, & Cue, 2005; McCarthy et al, 2013). Of parents with a valid CAP abuse scale score, 60 parents (60% of full sample) had CAP abuse scale scores less than 166 and were deemed “low-risk” and 40 parents (40% of full sample) had CAP abuse scale scores equal to or greater than 166 and were deemed “high-risk.”…”
Section: Main Studysupporting
confidence: 91%
See 2 more Smart Citations
“…After omissions, data from 100 parents were included in the final sample. This rate of exclusion due to invalid CAP inventories is consistent with exclusion rates observed in previous research (e.g., Carr, Moretti, & Cue, 2005; McCarthy et al, 2013). Of parents with a valid CAP abuse scale score, 60 parents (60% of full sample) had CAP abuse scale scores less than 166 and were deemed “low-risk” and 40 parents (40% of full sample) had CAP abuse scale scores equal to or greater than 166 and were deemed “high-risk.”…”
Section: Main Studysupporting
confidence: 91%
“…One possibility is that high-risk parents were insensitive to the acquisition of any new evaluative child information. However, this interpretation seems unlikely given that CPA risk group differences are commonly observed from similar paradigms examining parents’ semantic inferences about children (c.f., Crouch et al, 2010; McCarthy et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crouch et al (2010) reported that parents high on risk for child physical abuse (CPA) inferred more traits from children's negative behaviors than from positive ones, and this difference was greater than for low CPA risk parents. McCarthy et al (2013) looked at STIs from children's behaviors in a PDP analysis of false recognition among parents at high versus low risk for CPA. Traits were positive or negative and either vaguely or strongly implied.…”
Section: Spontaneous Inferences From Behaviorsmentioning
confidence: 99%
“…The study targeted specific variables, which could enable professionals to select groups of parents at greater require of participating in abuse prevention programs. McCarthy et al (2013) investigated whether parents at high-risk for child physical abuse (CPA) varied from low-risk parents in their likelihood to infer positive traits and negative traits from children's behaviors. They examined the contributions of automatic processes and controlled processes to task performance based on process dissociation procedures.…”
Section: Introductionmentioning
confidence: 99%